2016
DOI: 10.21608/jpp.2016.47036
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bud Dormancy for Flame Seedless Grapevine by Using Some Economic Sources.

Abstract: This study was carried out for two successive seasons (2013&2014) in a private vineyard located at Aga-Dakahlia Governrate to evaluate the efficiency of some new alternatives on dormancy breaking of Flame Seedless grapevines. The chosen vines were 5 years old, grown in a clay loam soil, spaced at 2x2.5m , irrigated by flood irrigation system .The vines were pruned during the second week of January for the two seasons of the study to obtain bud load of 72 buds/vine (6 canes x 12 buds/cane)and sprayed on the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…These results were true during the both seasons and cultivars. These findings are in line with those of Abo-ELwafa et al (2016) and Morsi and Seif El-yazal (2008) they stated that using of Garlic extract at 20% and Onion extract at 20 % were effective in enhancing chemical constituents of apple fruit as TSS and TSS/ acid ratio and decreased total acidity compared to the control. Figure (3) showed the effect of Garlic extracts and Clove oil as well as Hydrogen cyanamide at different concentrations used as bud breakage treatments on berries anthocyanin content of Flame seedless grape.…”
Section: -Ssc/acid Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…These results were true during the both seasons and cultivars. These findings are in line with those of Abo-ELwafa et al (2016) and Morsi and Seif El-yazal (2008) they stated that using of Garlic extract at 20% and Onion extract at 20 % were effective in enhancing chemical constituents of apple fruit as TSS and TSS/ acid ratio and decreased total acidity compared to the control. Figure (3) showed the effect of Garlic extracts and Clove oil as well as Hydrogen cyanamide at different concentrations used as bud breakage treatments on berries anthocyanin content of Flame seedless grape.…”
Section: -Ssc/acid Ratiosupporting
confidence: 90%
“…It is cleared that, vines sprayed by Hydrogen cyanamide at 2.5% (T 6 and T 11 ), Garlic at 10 and 15% combined with mineral oil 2% (T 7 and T 8 ) treatments showed the highest values followed by Garlic at 10 and 15% (T 2 and T 3 ) alone however, vines of control showed the lower concentration in both seasons. The enhancement effect of spraying with natural extracts and dormex may due to those effects on encouraging different vegetative growth parameters which increased carbohydrates accumulation Abo-ELwafa et al (2016). These results are in line with those of Sonego et al (2002) and Carvalho et al (2016) concluded that, natural and chemical bud break agents were very effective in hastening maturity and improving the yield and quality of the berries of 'BRS Rúbea' and 'BRS Cora' grapevines.…”
Section: -Ssc/acid Ratiosupporting
confidence: 68%